Supporting political violence: The role of ideological passion and social network. (December 2020) - Bélanger, Jocelyn J.; Robbins, Blaine G.; Muhammad, Hayat; Moyano, Manuel; Nisa, Claudia F.; Schumpe, Birga M.; Blaya-Burgo, Michelle
This research examines how social networks contribute to the process of radicalization, building on work showing that obsessive (vs. harmonious) passion for a cause is linked to greater support for political violence. Study 1 ( N = 331) shows that obsessive (vs. harmonious) passion is related to affiliating with radical (vs. moderate) social networks, which in turn is associated with support for political violence. Study 2 ( N = 381) provides experimental evidence for this phenomenon, by showing that inducing an obsessive mindset produces a greater proclivity to connect with radical activists, which in turn is associated with greater support for political violence. Drawing from social network analysis, Study 3 ( N = 366) shows that network density intensifies obsessively passionate individuals' affiliation to radical networks. The results offer insight into the group processes behind radicalization across different cultural contexts and ideologies.